An Integrated Mobile and Web Based Approach for Promoting Antenatal and Postnatal Care Patronages and Reduction of Maternal and Neonatal Mortality Rates: A Case Study of Yobe State - Ahmed, BS; Bara, MW (International Journal of Computer Sciences and Engineering, 2021)
Yobe State offers free antenatal and postnatal care services to target clients (pregnant women and nursing mothers). This free service was aimed to fulfil the MDGs fifth Goal to reduce maternal and infant mortality rates. However, the service is facing challenges of lack of patronage at the side of the clients. Researches show that, there exists a communication gap between the programme and the clients. Another problem is lack of maternal education from the clients. Some researchers have used ICT methods to solve this type of problems, however, most of the methods applied by the researchers in solving the problems are not cost-effective and skew to favour clients in urban areas. This research used the recent Information and Communication Technologies (ICT) methods to create an integrated platform that comprises Mobile and Web-Based (iMOWBA) to enhance the participation of clients regarding antenatal and postnatal care services. The platform provides different ways of delivering maternal awareness that include Web-based, mobile App, USSD Code and SMS. The technologies used include PHP, MYSQL, JavaScript, HTML and RapidSMS. The platform has increased the ANC services patronage from 46% to 67% of completed rounds.